On the Concept of Emphatic Rheme - Mkhitarian, Yelena (Armenian Folia Anglistika, 2005)
Distinction is an efficient syntactic device which helps highlight the rhematic part of an utterance in a most expressive way separating it from the core of the sentence and presenting it either fully or partially. In certain cases, the distinction can be so influential that it can bring about semantic changes in the structure singled out.